Multi-tier supply chain behavior with blockchain technology: Evidence from a frozen fish supply chain - Tokkozhina, U.; Martins, A.; Ferreira, J. (Operations Management Research, 2023)
Relationships in multi-tier supply chains (MTSCs) are complex and require constant information sharing. For MTSCs involved in perishable product distribution, blockchain technology (BCT) is one of the most promising technologies that can ensure products’ traceability and safety. This study examines a Portuguese MTSC for frozen fish products piloting BCT adoption for its supply chain (SC) practices. The goal is therefore to explore the consequences of information availability inherent for BCT adoption pilots in the SC context. This study follows a mixed-method approach, with qualitative and quantitative data collection techniques. Three semi-structured interviews with players from a single frozen fish SC, including supplier, transporter, and retailer were conducted. MAXQDA Analytics Pro 2022 software was used for further coding and data analysis. An online survey among retail chain consumers was conducted resulting in 112 responses. Regression analysis and Pearson correlation test were further performed via IBM SPSS Statistics software. Data collection for both parts took place between December 2021 and July 2022. This study explores four layers in the SC– including supplier, transporter, retailer and final consumer. Findings revealed a current lack of extensive and detailed information from upper tiers regarding products’ characteristics. Despite being hyped as a “trust-enabling” technology, BCT was found not to eliminate the need for trustful relationships between players prior to adoption, as information input requires human intervention. Even in those cases when the traceability option is not of major interest to final consumers, findings revealed a higher probability of purchasing fish products that have traceable information available.